CALCULATION OF OIL CHANGE INTERVALS IN DIESEL-BASED GAS ENGINES - Utaev, Sobir (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
Ensuring the reliability of internal combustion engines during operation requires a comprehensive approach, addressed in various areas. Addressing these issues is a pressing, complex task. The main factors include operating conditions, the type of fuel used, monitoring engine oil performance, and developing validated service life estimates. In maintaining the performance properties of engine oils, monitoring the key characteristics of the oil and justifying replacement intervals is essential.